Agricultural innovation system: analysis from the subsystems of R&D, training, extension, and sustainability - Gutiérrez Cano, Luis Fernando; Zartha Sossa, Jhon Wilder; Orozco Mendoza, Gina Lía; Suárez Guzmán, Lina María; Agudelo Tapasco, Diego Alejandro; Quintero Saavedra, Jorge Iván (Frontiers in Sustainable Food Systems, 2023)
The challenges faced by agricultural innovation systems (A.I.S.) are complex to solve, however, the authors consider that understanding the processes of innovation and development (R&D), sustainability, use of information and communication technologies, training, and outreach, as the focus of discussion in this review, have great potential to close the gaps in the system; as well as exploring strategies, projects and best practices that dynamize the operation of the system. The objective of this article is to review the literature on A.I.S.A. to identify its obstacles, challenges, and solution to close its gaps. The methodology identified the critical factors of system monitoring and defines search suitability to obtain 55 documents. With the results, a qualitative analysis is conducted on the mentioned axes, which is complemented with the text mining software Vantage Point V 15.1 to observe in graphical form the most relevant aspects. Within the conclusions is a constant demand from actors for access to information, and knowledge in the training processes, it is recommended in this regard the additional skills for innovation and participation in concerted practices. As regards the limitations of agricultural innovation processes, it suggests the involvement of cooperatives, technological platforms, and farmers’ organizations as intermediaries relevant to closing gaps. With regard to sustainability, A.I.S. thinking is recommended for an inclusive dialogue among actors and to facilitate sustainability transitions. Finally, to address the socio-technical and ethical challenges of access to technologies and technological transition, it is recommended to design appropriate policies for access to resources and the development of markets that enhance business opportunities and the development of sustainable innovations.